2014
DOI: 10.1111/inr.12087
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand nurses’ views on preceptoring international nurses

Abstract: Effective preceptorship requires training, recognition and support. Successful integration of international nurses depends on organizational recognition and implementation of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Friendliness shown by preceptors made it possible for IQNs to expose vulnerability. Riden et al’s () survey of 151 preceptors of IQNs in New Zealand drew attention to preceptors’ frustrations at their limited preparedness for this role, and the lack of recognition and workload adjustment. They considered that generic preceptorship courses were inadequate for successfully preceptoring IQNs.…”
Section: Power Distance and Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Friendliness shown by preceptors made it possible for IQNs to expose vulnerability. Riden et al’s () survey of 151 preceptors of IQNs in New Zealand drew attention to preceptors’ frustrations at their limited preparedness for this role, and the lack of recognition and workload adjustment. They considered that generic preceptorship courses were inadequate for successfully preceptoring IQNs.…”
Section: Power Distance and Acculturationmentioning
confidence: 99%
“…With internationally qualified nurses (IQNs) constituting an ever‐increasing proportion of the nursing workforce in developed countries, bridging programmes endeavour to enhance ‘cultural fit’ and readiness to practice in the new country (Khalili, Ramji, Mitchell, & Raymond, ; Riden, Jacobs, & Marshall, ; Sherwood & Shaffer, ; Tie, Birks, & Mills, ; Xu, ). However, research indicates that the transition process may extend well beyond an initial few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of an appropriate learning environment makes that new nurses are not interested to learn appropriate caring behaviours (Devi, Khandelwal, & Das, 2017). Other studies similarly reported that preceptors faced many limitations such as heavy workloads, taking various caring roles, lack of time for patient education, insufficient knowledge regarding educational methods and no support from nurse managers during the preceptorship programme (Liu, Lei, Mingxia, & Haobin, 2010;Riden, Jacobs, & Marshall, 2014). Chen et al (2011) in Taiwan confirmed the impact of time pressure on the preceptorship process.…”
Section: Discussionmentioning
confidence: 83%
“…Recommendations from this study were for specific training for IQN preceptoring within the national framework and better organisational support and recognition. An organisational and national preceptor register that would encourage quality assurance was also recommended (Riden et al, 2014).…”
Section: Iqns' Preparedness For Practicementioning
confidence: 99%
“…As IQNs make up 25% of the nursing workforce in NZ, then specific training appears warranted. NZ literature on IQN transition suggests that organisational and national registers for preceptors would encourage organisational accountability (Riden et al, 2014).…”
Section: Healthcare Agency Supportmentioning
confidence: 99%